UJI MUTU SIMPLISIA DAN EKSTRAK ETANOL 96% RIMPANG JAHE (Zingiber officinale Roscoe) - Efrilia, Mega; Chandra, Pra Panca Bayu; Endrawati, Santi (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Ginger (Zingiber officinale Roscoe) has long been commonly consumed as a spice and traditional medicine. The aim of the research was to test the quality of simplicia and ginger rhizome extract. The testing procedure consists of preliminary quality testing, testing specific and non-specific parameters. Fresh ginger rhizomes are processed to become simplicia powder. The simplicia was extracted using the maceration method using 96% ethanol solvent, then concentrated until a thick extract was obtained. Simplicia and extracts are subjected to quality testing. The results showed that the level of foreign organic matter of simplicia was 1.34%, the fine degree of simplicia was 4/18 through mesh sieve number 4 100% and number 18 was 96%. Identity of the research sample Zingiber officinale Roscoe. The levels of compounds in simplicia that are soluble in water and ethanol are 16.86 ± 0.45% and 6.81 ± 0.23%. The levels of compounds in the extract that were soluble in water and ethanol were 13.55 ± 0.21% and 13.72 ± 0.16%. Drying loss of simplicia is 0.80 ± 0.52% and extract is 9.53 ± 0.25%. The water content for simplicia is 9.03 ± 0.64% and extract is 12.33 ± 1.53%. The specific gravity of the simplicia is 0.7849 ± 0.06 g/mL and the extract is 0.85 ± 0.09 g/mL. The total ash content of simplicia was 4.09 ± 0.97% and the extract was 3.63 ± 0.44%. The water-soluble ash content in simplicia is 2.17 ± 0.31% and the extract is 2.6 ± 0.26%. The insoluble ash content of simplicia acid was 1.11 ± 0.32% and the extract was 0.5 ± 0.46%. Testing the quality of simplicia and ginger rhizome extract met the requirements, namely all specific parameters as well as non-specific parameters (drying loss, total ash and acid insoluble ash).